2020
DOI: 10.3390/ijerph18010233
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effects of College-Based Lifestyle Modification Program for Menstrual Health of Young Adult Women with Irregular Menses: A Randomized Controlled Trial

Abstract: Purpose: This study was conducted to develop the ‘College-based Lifestyle Modification Program’ (College-based LMP) for young adult women with irregular menstruation and examine its effects after intervention. Methods: The College-based LMP consisted of small group education, individual physical exercise counseling/training, individual diet counseling, and feedback and support. Participants were comprised of 38 females who reported less than 10 irregular menstruations in a year and were randomly assigned to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The most effective interventions include applicable diet modifications, increased physical activity and exercise modifications, and strategies to maintain adherence ( 29 ). Lifestyle modifications also appear to draw the ovulation function ( 30 ) as well as the menstrual cycle ( 31 ) into a regular level, which subsequently increases the successful pregnancy rates in PCOS patients. The studies reported that almost half of the PCOS patients would gain improvement both in regular menstrual cycle and ovulation function depending on the lifestyle modifications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective interventions include applicable diet modifications, increased physical activity and exercise modifications, and strategies to maintain adherence ( 29 ). Lifestyle modifications also appear to draw the ovulation function ( 30 ) as well as the menstrual cycle ( 31 ) into a regular level, which subsequently increases the successful pregnancy rates in PCOS patients. The studies reported that almost half of the PCOS patients would gain improvement both in regular menstrual cycle and ovulation function depending on the lifestyle modifications.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely acknowledged that obesity is a vital mediator in the development of PCOS. The level of sex-hormone-binding globulin is decreased in obese females ( 31 ), resulting in elevated androgen in the circulation and then in the target tissue, which disrupts normal ovulatory function ( 32 ). Additionally, obesity is associated with an elevated risk of metabolic syndrome, diabetes mellitus (type 2 diabetes), and insulin resistance in female bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Eight (13.6%) studies limited the inclusion criteria by sex (female-only participants) ( 29 , 40 , 56 , 58 , 70 , 79 , 83 , 88 ). Almost half of the studies ( n = 26, 44.1%) had further student-related inclusion/exclusion criteria ( 29 , 33 35 , 37 – 40 , 42 , 47 , 49 51 , 57 , 58 , 64 , 65 , 68 , 69 , 74 , 75 , 77 , 82 , 84 , 87 , 89 ), e.g., being a full-time student, undergraduate or graduate student, being a first-year student, and/or students enrolled in a specified university course.…”
Section: Resultsmentioning
confidence: 99%
“…In total, there were 92 intervention arms across the 59 studies. Of the 92 interventions, dietary behaviors were most commonly targeted ( n = 40, 43.5%) ( 29 , 31 , 32 , 34 , 37 , 38 , 40 – 42 , 47 , 50 , 51 , 53 , 56 , 57 , 59 62 , 70 , 71 , 75 , 78 , 79 , 82 , 84 , 86 89 ) followed by physical activity ( n = 39, 42.4%) ( 32 , 34 , 35 , 37 , 38 , 40 , 42 , 47 , 50 , 51 , 53 , 57 , 59 , 60 , 62 , 70 , 71 , 75 , 78 , 79 , 82 , 84 , 86 , 89 ), and alcohol intake ( n = 35, 38%) ( 34 , 36 , 42 44 , 48 , 52 , 54 , 60 , 64 66 , 68 , 69 , 72 74 , 83 , 84 , 86 , 87 ). Sedentary behavior ( n = 1, 1.1%) was the ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation